Median somatosensory evoked potential as a predictor of clinical outcome after urgent surgical extracranial internal carotid artery recanalization. Issue 2 (February 2021) - Ostrý, Svatopluk; Nevšímal, Milan; Nevšímalová, Miroslava; Reiser, Martin; Fiedler, Jiří
Highlights: Clinical outcome in patients with acute ischemic stroke due to extracranial internal carotid artery occlusion is most accurately predicted by the somatosensory evoked potential side-to-side amplitude ratio. An upper extremity motor deficit is incompatible with elicitability of the somatosensory evoked potentials in the acute phase. Median somatosensory evoked potentials may contribute to improving the indication for urgent internal carotid artery recanalization. Abstract: Objective: Changes in the N20/P25 amplitude of somatosensory evoked potentials (SEP) of the median nerve have been found to correlate with those in cortical regional cerebral blood flow (rCBF). Our study presents the use of median nerve SEP amplitude in predicting the clinical outcome of urgent surgical internal carotid artery (ICA) recanalization. Methods: A total of 27 patients suffering an acute ischemic stroke (AIS) with extracranial ICA occlusion within 24 h were prospectively recruited. The primary preoperative endpoints included the SEP amplitude absolute value (SEP-amp) and the SEP amplitude side-to-side ratio (SEP-ratio). Clinical outcome at 3 months postoperatively was assessed using the modified Rankin scale (mRS-3M). Results: The positive predictive values (PPVs) for SEP-amp and SEP-ratio were 95.5% and 100%, respectively, with the negative predictive values (NPVs) being 60.0% and 100%, respectively. The SEP-ratio correlated fully with mRS-3M. Conclusion: The median SEP side-to-side N20/P25 amplitude ratio seems to be a very strong positive and negative predictor of the clinical outcome of urgent recanalization of an extracranial ICA occlusion. Significance: The results suggest that cortical evoked activity may help in selection patient for surgical recanalization and predict clinical recovery after an acute ischemic stroke.